Association between anxiety, obesity and periodontal disease in smokers and non-smokers: A cross-sectional study - Abhay P. Kolte; Rajashri A. Kolte; Vrushali N. Lathiya (Tabriz University of Medical Sciences, 2016)
Background. Psychological stress is known to be a relevant risk factor for many inflammatory conditions, including periodontal disease. A few studies have probed the relationship between obesity and periodontal disease. Therefore this cross-sectional study was aimed to examine the relationship between psychological stress and obesity and periodontal disease in smokers and non-smokers. Methods. The participants included 90 patients, equally divided into three groups of non-smokers and periodontally healthy, non-smokers and smokers with untreated moderate-to-severe chronic periodontitis. Socioeconomic data, psychosocial measurements, physical parameters and clinical findings of PPD, CAL, PI and GI were recorded. Results. The clinical parameters were assessed for three groups in three different anxiety levels of mild, moderate and se-vere. Intra-group comparison of PPD and CAL in the three anxiety levels showed increased periodontal destruction with an increase in anxiety levels, the results being statistically highly significant for PPD differences in smokers (P < 0.0001). The mean differences in PPD and CAL in severe anxiety levels between smokers and non-smokers were 0.68 mm and 0.70 mm and both the findings were statistically significant. The mean PPD and CAL in smoker and non-smoker groups in obese patients was higher as compared to non-obese patients and the differences were highly significant (P < 0.001). Conclusion. The results of our study indicated a positive and strong correlation between anxiety, obesity and periodontal disease in smokers and non-smokers. Smoking appears to further attenuate this association.